1997
DOI: 10.1590/s0100-879x1997000300017
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis and acute arterial thrombosis in rabbits: a model using balloon desendothelization without dietary intervention

Abstract: Acute thrombosis can be induced in rabbits by a triggering protocol using Russell's viper venom and histamine given after 8 months of a 1% cholesterol diet and balloon desendothelization. In the present study, we tested the hypothesis that aortic desendothelization performed 4 months before the triggering protocol without a high cholesterol diet is a highly effective and less expensive way of producing arterial atherosclerosis and thrombosis. Nineteen male New Zealand white rabbits on a normal diet were studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…The area of endothelial damage in the control group (GC) was also limited to the region of the glue. Therefore, the cell damage could not have been caused by the balloon catheter technique but had to be due to the focal reaction, previously reported in association with adhesives [4,6,10]. Our short-term study showed an increasing inflammatory reaction over the 3-day postoperative period.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…The area of endothelial damage in the control group (GC) was also limited to the region of the glue. Therefore, the cell damage could not have been caused by the balloon catheter technique but had to be due to the focal reaction, previously reported in association with adhesives [4,6,10]. Our short-term study showed an increasing inflammatory reaction over the 3-day postoperative period.…”
supporting
confidence: 64%
“…The gap was most likely the reason for thrombus formation, as neither the anastomoses without a gap nor the glue control group (GC) developed a thrombus. Another possible explanation for thrombus formation could be the balloon catheter, which resulted in platelet-rich arterial thrombus formation in the studies by Picon et al [6] and Tepe et al [9]. However, we selected the length of the balloon to exceed the area to which the glue was applied and identified the endothelial damage only over the length of the applied glue.…”
mentioning
confidence: 99%
“…Russell's viper venom in a dose of only 150 μg/kg of body weight combined with histamine, an arterial vasoconstrictor in rabbits, can induce significant arterial thrombosis in rabbits withdamaged/atherosclerotic arteries. In these studies, the Russell's viper venom was used as a procoagulant and endothelial toxin, and endothelial injury plays a central role in these processes (Picon et al 1997). According to a study by Liau (1991), the average venom amount of a D.r.…”
Section: Resultsmentioning
confidence: 99%
“…RVV and intravenous histamine were used to produce plaque disruption and thrombosis in cholesterol fed rabbits after angioplasty injury. Recently, a variant of this model, using RVV alone without dietary intervention, has also been proposed (39) and aortic medial necrosis in the RVV rabbit model has, in addition, been the subject of a very recent study (40) assessing possible mechanisms of RVV-triggered arterial thrombosis. Our observations correlated well with the observations of Abela et al (31) and Constantinides and Chakravarti (30), demonstrating increased local foam cell invasion and intimal thrombosis in RVV and histamine-treated cholesterol fed rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…Serp-1 was purified from a recombinant Chinese hamster ovary cell line (Biogen, Inc., London, Canada) by affinity chromatography using linked monoclonal antibody (AXB7.9, courtesy of Dr. L. Ling, Biogen, Inc.) as previously described (29). The concentration of purified Serp-1 was determined by absorbance at 280 nM using a molar extinction coefficient of 32 700 M Ϫ1 /cm (37)(38)(39)(40)(41).…”
Section: Methodsmentioning
confidence: 99%